ZnO nanowires for solar cells: a comprehensive review. (21st June 2019) - Consonni, Vincent; Briscoe, Joe; Kärber, Erki; Li, Xuan; Cossuet, Thomas
Abstract: As an abundant and non-toxic wide band gap semiconductor with a high electron mobility, ZnO in the form of nanowires (NWs) has emerged as an important electron transporting material in a vast number of nanostructured solar cells. ZnO NWs are grown by low-cost chemical deposition techniques and their integration into solar cells presents, in principle, significant advantages including efficient optical absorption through light trapping phenomena and enhanced charge carrier separation and collection. However, they also raise some significant issues related to the control of the interface properties and to the technological integration. The present review is intended to report a detailed analysis of the state-of-the-art of all types of nanostructured solar cells integrating ZnO NWs, including extremely thin absorber solar cells, quantum dot solar cells, dye-sensitized solar cells, organic and hybrid solar cells, as well as halide perovskite-based solar cells.